The Students’ Perception on the Use E-LKPD Liveworksheets.com in Learning English to Informatic Engineering Students of Politeknik Sawunggalih Aji - Wicaya Ningrum, Desi Innanti (Politeknik Sawunggalih Aji, 2024)
Technology has already been part of education in the teaching and learning process. Hence, to support the successful of teaching and learning, the lecturers are required to master technology especially in delivering material, giving assignments, and assessing learning process. To overcome the problems, lecturers can use digital teaching materials by the use of electronic student worksheet (E-LKPD). One of the platforms that support E-LKPD is Liveworksheets.com. The objective of the study is to describe students’ perception of using E-LKPD Liveworksheets.com that is focused in learning grammar. The research sample used was the fifth semester students of informatic engineering. This research used descriptive with quantitative method. Questionnaire was used to collect the data. The questionnaire consists of 9 statements that were divided into; Perceived Usefulness, Perceived Ease of Use, and Attitude Toward Use. The results of this study show that students have good perceptions on the usefulness of using E-LKPD Liveworksheets.com in learning grammar because they can learn grammar effectively and efficiently. The students have very good perceptions of the Perceived Ease of Use in doing E-LKPD Liveworksheets.com because its flexibility and features to learn and work on grammar. Last, students have good perceptions in using E-LKPD Liveworksheets.com for learning English based on Attitude Toward Use.